The Impact of Mind Map as Project-Based Learning on Arabic Vocabulary Learning Outcomes at Ma’had Babul Khairat - Khaerah, Miftahul; Muassomah, Muassomah; Afifah, Afifah; Fitra, Muh. Naufal; Maidah, Nur; Sya'rawi, Muhammad Irham (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
Although vocabulary learning is a fundamental aspect of Arabic language acquisition, it is often perceived as monotonous and ineffective, particularly in Ma’had settings where access to technological resources is limited. This study explores the implementation of a project-based learning (PBL) model using mind maps to improve Arabic vocabulary learning and examines students' responses to this pedagogical approach. A descriptive qualitative method was employed, focusing on female students at Ma’had Babul Khairat. Data were gathered through observations, questionnaires, and documentation, and analyzed using Miles and Huberman's framework, which involves data reduction, data presentation, and conclusion drawing. The findings reveal that the PBL model integrated with mind maps offers an innovative and effective solution for Arabic vocabulary acquisition in resource-constrained settings. Students reported that the approach was engaging and interactive, making it easier to remember and internalize vocabulary. Additionally, the use of mind maps significantly enhanced their motivation, interest, and active participation in the learning process. The method also encouraged collaboration and creativity among students, fostering a more dynamic and student-centered learning environment. These results highlight the potential of project-based learning with mind mapping as a practical pedagogical tool in Ma’had settings. This model not only addresses the challenges of traditional vocabulary learning but also contributes to the development of innovative teaching strategies that align with the needs and preferences of students in such educational contexts